2019
DOI: 10.1051/0004-6361/201935904
|View full text |Cite
|
Sign up to set email alerts
|

Long-term optical spectroscopic variations in blazar 3C 454.3

Abstract: Aims. Characterisation of the long-term variations of the broad line region in a luminous blazar, where Comptonization of broad line emission within a relativistic jet is the standard scenario for production of γ-ray emission that dominates the spectral energy distribution. Methods. We analyse 10 years of optical spectroscopic data from the Steward Observatory for the blazar 3C 454.3, as well as γ-ray data from the Fermi Large Area Telescope. The optical spectra are dominated by a highly variable non-thermal s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 60 publications
4
12
0
Order By: Relevance
“…In the SWIFT/UVOT grism monitoring of NGC 5548, Cackett et al (2015) showed that the Mg II emission line is not strongly correlated with the continuum variability, and there is no significant lag between the two. However, more recent studies of CTS C30.10 (radio quiet quasar) and 3C 454.3 (blazar) Czerny et al (2019) and Nalewajko et al (2019) show that there are time delays of 562 +116 −68 and ∼600 days, respectively, between the continuum variations and the response of the Mg II emission line. León-Tavares et al (2013) and Isler et al (2013) reported the statistically significant flare-like event in the Mg II emission line in the blazar 3C 454.3.…”
Section: Mg II and Fe Ii Variabilitymentioning
confidence: 98%
“…In the SWIFT/UVOT grism monitoring of NGC 5548, Cackett et al (2015) showed that the Mg II emission line is not strongly correlated with the continuum variability, and there is no significant lag between the two. However, more recent studies of CTS C30.10 (radio quiet quasar) and 3C 454.3 (blazar) Czerny et al (2019) and Nalewajko et al (2019) show that there are time delays of 562 +116 −68 and ∼600 days, respectively, between the continuum variations and the response of the Mg II emission line. León-Tavares et al (2013) and Isler et al (2013) reported the statistically significant flare-like event in the Mg II emission line in the blazar 3C 454.3.…”
Section: Mg II and Fe Ii Variabilitymentioning
confidence: 98%
“…A positive correlation in the α − log L 5100 relation is found with r s = 0.43 and a p-value of 10 −13 . Therefore, a "redder when brighter" (RWB) trend is observed in PKS 1510, indicating the presence of an accretion disk in the continuum (e.g., Gu et al 2006;Nalewajko et al 2019).…”
Section: Variabilitymentioning
confidence: 98%
“…For example, Zhang et al (2019) performed a reverberation study of FSRQ 3C273 using ten years of Steward Observatory monitoring data, which provide a highly reliable measurements of BLR size. Nalewajko et al (2019) performed Mg II reverberation studies of FSRQ 3C 454.3 using the Steward Observatory monitoring…”
Section: Introductionmentioning
confidence: 99%
“…10 −13 . Therefore, a "redder when brighter" (RWB) trend is observed in PKS 1510 indicating the presence of accretion disk in the continuum (e.g., Gu et al 2006;Nalewajko et al 2019).…”
Section: Variabilitymentioning
confidence: 99%
“…For example, Zhang et al ( 2019) performed a reverberation study of the FSRQ 3C273 using 10-yr long Steward Observatory monitoring data providing a highly reliable measurement of BLR size. Nalewajko et al (2019) performed Mg II reverberation studies of FSRQ 3C 454.3 using the Steward Observatory monitoring data and Zajaček et al (2020) measured Mg II lag of HE 0413-4031 using SALT monitoring data.…”
Section: Introductionmentioning
confidence: 99%